Perbandingan Perceived Service Quality PT. Pos Indonesia, JNT dan JNE pada Pengguna Layanan Logistik Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Yulia, Safina; Jalil , Ivon; Chairiyaton, Chairiyaton (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to identify and analyze the comparison of perceived service quality among three courier service companies, namely PT. Pos Indonesia, JNT, and JNE, in Johan Pahlawan District, West Aceh Regency. The method used is quantitative with a comparative quantitative approach. Data were collected through a Likert scale (1–5) questionnaire from 96 respondents who had used services from the three companies. Validity and reliability tests were conducted to ensure the research instrument was appropriate. The data were then analyzed using one-way ANOVA and Post Hoc Bonferroni tests. The results indicate a significant difference in perceived service quality among the three companies (p = 0.000 < 0.05). JNT obtained the highest average score, followed by JNE, while PT. Pos Indonesia received the lowest. The Post Hoc test results showed that all pairwise comparisons (JNT vs. JNE, JNT vs. PT. Pos Indonesia, and JNE vs. PT. Pos Indonesia) had significant differences. These findings align with the Logistics Service Quality (LSQ) theory, which emphasizes the importance of effective logistics services in shaping customer perceptions. This research implies that logistics service providers must continuously improve service quality based on customer needs and expectations, particularly in aspects such as delivery speed, clarity of information, and complaint handling. For PT. Pos Indonesia, these findings can serve as a foundation for evaluating and enhancing competitiveness in an increasingly competitive logistics market.